Inorganic membrane: a game changer for gas separation and purification - Kurniawan T.A.; Riaz M.; Mohyuddin A.; Haider A.; Ali S.; Abdulkareem-Alsultan G.; Othman M.H.D.; Goh H.H.; Anouzla A.; Al-Hazmi H.E.; Aziz F.; Wibisono Y.; et al. (Springer Science and Business Media Deutschland GmbH, 2025)
This review explores the advancements and remaining challenges in inorganic membrane science, particularly focusing on their potential for industrial applications. It delves into the fundamental principles of inorganic membrane design, fabrication, and characterization techniques. The review alsocritically analyzes key challenges faced by inorganic membranes, such as physical aging, plasticization, defective formation, and fouling. Strategies for overcoming the limitations to enhance permeability and long-term stability are discussed. Specific examples are provided to illustrate the applications of inorganic membranes in gas separationand wastewater treatment, emphasizing their high chemical stability, as compared to conventional polymeric membranes. The energy efficiency of inorganic membranes for volatile organic compound (VOC) removal at ambient temperatures is highlighted with PDMS (polydimethylsiloxane) serving as an example for removing toluene, xylene, and acetone from gas streams. Finally, the review assesses future research directions to further enhance the engineering applicability of inorganic membranes for wastewater treatment and gas separation, solidifying their position as a promising technology for diverse industrial processes. ? The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.